2014
DOI: 10.1523/jneurosci.1366-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Brain Differences in 16p11.2 Deletion and Duplication Carriers

Abstract: Deletions and duplications of the recurrent ϳ600 kb chromosomal BP4 -BP5 region of 16p11.2 are associated with a broad variety of neurodevelopmental outcomes including autism spectrum disorder. A clue to the pathogenesis of the copy number variant (CNV)'s effect on the brain is that the deletion is associated with a head size increase, whereas the duplication is associated with a decrease. Here we analyzed brain structure in a clinically ascertained group of human deletion (N ϭ 25) and duplication (N ϭ 17) car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
179
5
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(196 citation statements)
references
References 63 publications
11
179
5
1
Order By: Relevance
“…heterozygous deletions and duplications exhibited abnormal brain volumes, with the largest effect detected in the thalamus, and trends in cerebellum and hippocampus (Qureshi et al 2014). Diffusion tension imaging analyses revealed white matter abnormalities in 16p11.2 deletion carriers, especially in the anterior corpus callosum, and bilateral internal and external capsules (Owen et al 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…heterozygous deletions and duplications exhibited abnormal brain volumes, with the largest effect detected in the thalamus, and trends in cerebellum and hippocampus (Qureshi et al 2014). Diffusion tension imaging analyses revealed white matter abnormalities in 16p11.2 deletion carriers, especially in the anterior corpus callosum, and bilateral internal and external capsules (Owen et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…16p11.2 deletion syndrome presents with a range of mild-to-severe cognitive impairments, with IQ scores averaging 2 SDs lower than controls, and a confirmed diagnosis of autism in 15% of affected individuals (Hanson et al 2010Zufferey et al 2012;Qureshi et al 2014). 16p11.2 deletion carriers are affected in multiple cognitive domains, including verbal and nonverbal IQ, cognitive flexibility, and spatial working memory (Hanson et al 2010Stefansson et al 2014;Moreno-De-Luca et al 2015).…”
mentioning
confidence: 99%
“…[2][3][4][5][6][7] They are associated with Rolandic epilepsy 8 and mirror phenotypes on body mass index (BMI), head circumference (HC), and brain volume. [9][10][11][12] The deletion of the distal 16p11.2 220 kb BP2-BP3 locus (MIM: 613444) is likewise enriched in individuals with early-onset obesity and is also associated with developmental delay, intellectual disability, autism spectrum disorders (ASD), and schizophrenia. 3,[13][14][15][16] Moreover, the BP2-BP3 deletion and reciprocal duplication have mirror effects on BMI and HC, whereas the duplication of this interval, like the deletion, is associated with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…In one study using sMRI (Qureshi et al, 2014), a mirror phenotype of brain volume was observed for individuals with ASD and a copy number variation within the 16p11.2 locus, such that compared to controls, deletion carriers exhibited increases and duplication carriers exhibited decreases in brain size. Other work has associated autism risk genes to structural and functional brain connectivity (e.g., CNTNAP2) (Dennis et al, 2011;Rudie et al, 2012).…”
Section: Imaging Datamentioning
confidence: 99%